ADAPTATION AND VALIDATION OF THE ATAMS SCALE (ATTITUDES TOWARD ANGER MANAGEMENT) IN INDONESIAN LANGUAGE: A REVIEW THROUGH EXPLORATORY FACTOR ANALYSIS (EFA) - Okta Fatonah, Sabrina; Fhanesa Fatma Kharuniaesa; Devi Lusiria (Causalita, 2026)
This study aims to adapt and validate the Attitudes Toward Anger Management Scale (ATAMS) into the Indonesian language and to examine its psychometric properties through Exploratory Factor Analysis (EFA). Anger is a common emotional experience that, if not properly managed, may lead to negative psychological and social consequences. However, cultural barriers and stigma often inhibit individuals in Indonesia from seeking professional help for anger management. The adaptation process followed the International Test Commission (ITC) Guidelines, involving forward-backward translation and expert judgment. The study involved 334 Indonesian participants aged 19 years and above. The results showed that the Indonesian version of the ATAMS consists of two main factors, consistent with the original scale: Belief in Treatment and Receptiveness. The scale demonstrated good reliability with Cronbach’s alpha of 0.777, and factor loadings met acceptable criteria. Furthermore, the findings suggest that this adapted scale is appropriate for use in the Indonesian cultural context, providing a reliable tool for both researchers and practitioners to assess individuals’ attitudes toward seeking professional anger management interventions.